The role of an entity registry in scholarly communication: exploring creative uses of research activity data - Rumsey, S; Loureiro-Koechlin, C (Routledge, 2010)
The Oxford University Research Archive (ORA) is the University's open access repository for research outputs. To simplify deposit in ORA, a registry has been created containing data harvested from existing sources to be used as repository metadata. The registry stores publicly available research activity data, that is, data about research including people, projects, and funders. Data held in the registry are available for purposes beyond the repository, particularly as the registry uses semantic web technologies which expedite data sharing. Value is added by aggregating disparate data for discovery, by making creative use of data such as revealing connections between entities and recording data provenance. This article describes the entity registry, its role within ORA, and as a tool to support scholarly communication. The advantages of storing data as entities and gathering, aggregating, and displaying research activity data to assist dissemination of research are explained. Examples of use of the registry and its data are provided that enable easy discovery of researchers and their activities and reveals hidden connections between them, thereby, encouraging communication and collaboration between different subject areas. Development of the registry and examples has been underpinned by extensive stakeholder analysis and user testing.